Strategic management research in the public sector: A review, synthesis, and future directions - Poister, Theodore H.; Edwards, Lauren Hamilton; Pitts, David W. (2010)
Although there is considerable literature on strategic planning and management in the public sector, there has been little effort to synthesize what has been learned concerning the extent to which these tools are used in government, how they are implemented, and the results they generate. In thi article, the authors review the reearch o strategic planning and management in the public sector to understand what has been learned to date and what gaps i knowledge remain. In examining the 34 research articles in this area published in the major public administratin journals over the past 20 years, the authors find substantial empirical testing of the impacts of environmental and institutional/organizational determi nants on strategic management but efforts to assess linkages between strategic planning processes and organizational outcomes or performance imporovements are sparse. Lage N quantitative analyses and comparative case studies could improve the knowledge base in this critical area. - Reproduced.
Keywords: Public administration